Surface electromyography of facial muscles during natural and artificial feeding of infants - Gomes, Cristiane F. [UNESP]; Trezza, Ercília M. C. [UNESP]; Murade, Emílio C. M.; Padovani, Carlos R. [UNESP] (Fundacao Sociedade Brasileira de Pediatria, 2006)
Objective: To measure and compare the activity of the masseter, temporalis and buccinator muscles in different infant feeding methods. Method: Cross-sectional study of 60 full-term infants with no intercurrent diseases, aged between two and three months, classified into the following groups: 1) exclusive breastfeeding; 2) breastfeeding plus bottle-feeding; and 3) exclusive breastfeeding plus cup feeding. Surface electromyography was performed during infant feeding. The Krushal-Wallis test was used, complemented by multiple paired comparisons of the groups. A 5% significance level was chosen for the tests. Results: Statistically higher results were verified in the breastfeeding group in relation to the bottle-feeding one, both in the range of movement and the mean contraction of the masseter. With regard to the temporalis muscle, statistically higher results were found in the breastfeeding group comparatively to the bottle-feeding one. As to the buccinator muscle, statistically higher results were observed in the breastfeeding group in relation to the bottle-feeding one, although in this case, the difference concerned only the range of contraction. Conclusion: The similarities between the muscle activity in the breastfeeding and in the cup-feeding groups suggests that cup-feeding can be used as an alternative infant feeding method, being better than bottle-feeding, due to the hyperactivity of the buccinator muscle, which could result in changes to the structural growth and development of the stomatognathic system functions. Copyright © 2006 by Sociedade Brasileira de Pediatria.
Keywords: Breastfeeding; Electromyography; Facial muscles; Infants; Sucking; artificial feeding; bottle feeding; breast feeding; clinical trial; comparative study; controlled clinical trial; controlled study; double blind procedure; electromyography; face muscle; feeding behavior; female; health survey; human; infant; infant feeding; male; masseter muscle; muscle contractility; muscle function; orbicularis oris muscle; statistical analysis; statistical significance; temporalis muscle; Age Distribution; Bottle Feeding; Breast Feeding; Cross-Sectional Studies; Double-Blind Method; Facial Muscles; Female; Humans; Infant; Male; Milk, Human; Pacifiers; Statistics, Nonparametric; Sucking Behavior